2012
DOI: 10.2478/s11756-011-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of probiotics and natural bioactive compounds in modulation of the common molecular pathways in pathogenesis of atherosclerosis and cancer

Abstract: Atherosclerosis and cancer are ranked among the most serious health problems in human medicine. Various predictive and etiological factors, biomarkers and molecular pathways of disease development and progression common to atherosclerosis and cancer suggest that the two most common diseases in worldwide dimension are far more closely aligned than previously believed. It is hypothesized that atherosclerosis and cancer are variants of a similar disease process. Shared disease progression in atherosclerosis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 105 publications
0
7
0
2
Order By: Relevance
“…Dairy products are an important source of protein and certain vitamins and minerals, such as vitamin D, vitamin A and vitamins B-12, B-6 and calcium (36). Use of dairy products, especially fermented products containing probiotics is important since probiotics have both local and general biomedical effects, inhibitory effect against pathogens, optimising effect on digestive processes, immunostimulative effect as well as anti-tumour and cholesterol-reducing activities (37).…”
Section: Discussionmentioning
confidence: 99%
“…Dairy products are an important source of protein and certain vitamins and minerals, such as vitamin D, vitamin A and vitamins B-12, B-6 and calcium (36). Use of dairy products, especially fermented products containing probiotics is important since probiotics have both local and general biomedical effects, inhibitory effect against pathogens, optimising effect on digestive processes, immunostimulative effect as well as anti-tumour and cholesterol-reducing activities (37).…”
Section: Discussionmentioning
confidence: 99%
“…Synbiotics (a combination of probiotics and prebiotics) improve survival of probiotics enhancing their effects in the large bowel (Roberfroid, 2000). Several studies have shown additional benefits of probiotics, such as the increase in immune system response and the release of bioactive compounds (Hempel et al, 2012;Bomba et al, 2012). The release of bioactive peptides from a protein sequence can be produced by enzymatic hydrolysis (Udenigwe & Aluko, 2012;Hartmann & Meisel, 2007), by fermentation processes (Hafeez et al, 2014;Udenigwe & Aluko, 2012;Quirós et al, 2005), or by a combination of both and during gastrointestinal digestion of food (Saito, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Для визначення біосумісності препаратівпробіотиків з автохтонноїю мікробіотою необхідно проводити ряд досліджень для конкретного індивідуума, або розробляти аутопробіотики, що є досить складним процесом. У зв'язку з цим, фахівці покладають великі надії на групу метаболітних про-і синбіотиків, які в порівнянні з клітинною формою більш стабільні при зберіганні, не знижують свою біологічну активність при застосуванні на тлі лікувального курсу антибіотиків, не спричиняють побічних дій на організм людини при гострих запальних процесах і хронічних захворюваннях, на відміну від живих мікроорганізмів (Di Caro et al, 2005;Chang et al, 2009;Bomba et al, 2012;Bourdichon et al, 2012).…”
Section: вступunclassified